Hak Waris Anak yang Berbeda Agama dengan Orang Tua Dalam KUH Perdata dan Kitab Hukum Islam - Aina Kholilah Lubis; Nursaidah Rambe; Fauziah Lubis (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
This study aims to analyze the arrangements regarding the inheritance rights of children of different religions according to code of Civil law and Islamic law and settlement efforts regarding the distribution of inheritance rights of children of different religions according to Islamic law and code of Civil law.The results showed that the regulation regarding the inheritance rights of children of different religions according to Islamic law is regulated in the hadith and KHI in which non-Muslim children are not entitled to inheritance. However, in practice, in court decisions the judge still gives a share of the inheritance to children of different religions based on a compulsory will. This is against the requirements of Islam and KHI. However, the decision to grant the inheritance is to realize justice, benefit and legal certainty infamily life.Meanwhile, wills are used by judges in court decisions regarding the distribution of inheritance assets. Keywords: Inheritance Rights; Children Of Different Religions; Code of Civil law